TO THE STUDY OF THE FLOCCULATION AND COAGULATION PROCESS IN THE PURIFICATION OF WATER FOR INDUSTRIAL APPLICATION - ONYSHCHUK, Oksana (Herald of Khmelnytskyi National University. Technical sciences, 2023)
It is an important criterion the choice of lighting technique for industrial applications in water purification. In the article it was examined the research methods of the coagulation and flocculation process. Today, the improvement of these techniques and the use of flocculants and coagulants, which speed up the process of coagulation and flocculation, are relevant. It were considered as coagulants sulfuric acid salts Al2(SO4)3 and FeSO4. It was noted an advantage over aluminum salts since iron salts which can be used to purify water with different salt composition and different pH values, which work better at low temperatures, and are characterized by greater strength and grain size. It was considered the application and influence of the cationic flocculant "PuroFloc 890" or the anionic "Flopam", which allow water clarification without the use of a coagulant. It was determined and considered the process of coagulant formation. Methods and processes for the intensification of the separation process have been studied, including due to the thickening of particles in the aggregate under the action of coagulants and flocculants (coagulants), separation of the liquid and solid phases. It was found that the advantage of the resulting suspended layer is that it works like a filter, removing fine particles from the water. As the particles accumulate, their concentration increases and the phenomenon of compressed deposition occurs, in which the deposition rate decreases because energy was spent on friction. It is necessary to reduce the speed of the upward flow to reduce the productivity of the illuminator,